Impact of contaminants bound to suspended particulate matter in the context of flood events - Wölz, Jan; Fleig, Michael; Schulze, Tobias; Maletz, Sibylle; Lübcke-von Varel, Urte; Reifferscheid, Georg; Kühlers, Dirk; Braunbeck, Thomas; Brack, Werner; Hollert, Henner (Journal of soils and sediments, 2010)
The presented study investigated on contamination of suspended particulate matter (SPM) in rivers that was sampled long-term and with higher frequency during a flood event at the river Rhine. It was conducted to determine in vitro biological effects as well as to identify and quantify compound classes and effective contaminants. Research was part of investigation on hazards of contaminants bound to SPM to inundated sites and retention areas that are inundated during flood events.
Gesehen am 15.03.2024